OP126 The European Network For Health Technology Assessment (EUnetHTA) Template To Aid Health Technology Assessment-based Decisions. (2017) - Ballini, Luciana; Bonvicini, Laura; Rossi, Paolo Giorgi; Vicentini, Massimo
Abstract : INTRODUCTION: Health professionals often advocate and request innovative health technologies, perceiving Health Technology Assessment (HTA) as a delay or counterargument to their requests. To facilitate engagement of professionals and decision makers in the HTA process and endorsement of process outputs, a system for technology requests submission, based on the European Network for HTA (EUnetHTA) Submission Template, was established and subsequently piloted in a cancer research institute. METHODS: The "EUnetHTA medical devices evidence submission template" for companies (1) was adapted for use by professionals proposing a health technology for acquisition. Adaptation consisted mainly in: re-arrangement of chapters order with emphasis on the health problem, unmet needs, claimed additional benefits of the technology and potential for research; inclusion of information on costs/financial resources; and inclusion of a summary with a pre-defined set of brief statements to inform appraisal. The headings for the nine one-paragraph statements were: relevance of the health problem; degree of innovativeness of the technology; potential clinical impact; potential research relevance; comparative safety and effectiveness; economic impact; organizational impact; availability/quality of scientific literature; and degree of diffusion. Decision makers discussed the appraisal's statements with the proponents before reaching a conclusion. RESULTS: From January 2016 technology requests were examined only if presented through the submission template. Results from submissions of three innovative technologies for prostate cancer treatment, endovascular procedures and cataract surgery will be discussed. Acceptability of the submission template was high and professionals — supported by experts available in their institution (clinical engineers, epidemiologists and others) — were successful in completing the dossier. Decision-makers appraisal proved facilitated and transparent. Concerted decisions were taken within a few weeks from submission. CONCLUSIONS: The EUnetHTA tool proved flexible and valuable to initiate an HTA-based decision-making process. Appraisal was cooperative and proponents were involved in the decisions, through a process requiring a mean total time of 6 months. Participants' misgivings were overcome by transparency and objectivity of the process.